Integrating physical activity and Edupas-based STEAM-SDGs for students’ sustainability awareness in vocational education - Muhammad Syaipul Hayat; S. Sumarno; Noora Qotrun Nada; Mahmud Yunus (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Applying STEAM in vocational learning needs to be integrated with Sustainable Development Goals (SDGs) values. Physical activities have been recognized as significant contributors to achieving SDGs because can boost students' awareness and commitment towards sustainable development goals.